International Strategy on Market Selection, market entry mode and risk analysis - Wong, Sing Lung. (2004)
The objective of this paper is to study the international market selection program by Malaysian firms engaging in international business. It will analyze and identify the factors of importance or screening criteria in evaluating potential foreign markets.